DEVELOPING AN IMPROVED MEASURE OF EARNINGS MANAGEMENT - Yao Tian (STIE Malangkucecwara, 2022)
Over the last 30 years, researchers have developed different approaches to measure earnings management. This study builds on prior research and combines the total accrual approach and the earnings distribution after management approach to develop a more accurate measure of earnings management. Empirical results show that this refined measure developed in this study is able to more precisely identify firms that manipulated earnings (manipulators) and firms that did not manipulate earnings (non-manipulators). This contributes to the earnings management literature a more accurate measure of earnings management to meet or beat a specific earnings benchmark. The results of this paper has practical implications. In particular, practitioners (financial analysts and investors) can use the new measure developed in this study to more accurately detect firms' earnings management activities. This enables practitioners to better interpret firms' financial statements and earnings news.